Development of an epitope-based vaccine inhibiting immune cells rolling and migration against atherosclerosis using in silico approaches. (October 2017) - Tourani, Mehdi; Karkhah, Ahmad; Najafi, Ali
Graphical abstract: Highlights: We designed an epitope-based vaccine against atherosclerosis for diapedesis inhibition. CD99, CD81 and CD99L2 proteins are the most important antigens involved in diapedesis. Diapedesis is a key way in initiation of atherosclerosis-related inflammation. Our analysis revealed that the modeled vaccine had appropriate properties and can properly stimulate the responses of T and B cells. Abstract: Atherosclerosis is a chronic inflammatory disease characterized by formation of pro-oxidative lipids in large and medium-sized vessels. Over the years, many treatments and drugs have entered the market to improve atherosclerosis and autoantigen-mediated active immunization is currently considered as a beneficial method. Therefore, this study was conducted to design a novel epitope-based vaccine against atherosclerosis employing CD99, CD81 and CD99L2 antigens. In this way, structural vaccinology approaches were used to design a novel multi-epitope vaccine against atherosclerosis. Six epitopes were predicted from CD99, CD81 and CD99L2 proteins. In addition, helper epitopes selected from Tetanus toxin fragment C (TTFrC)ion were applied to induce CD4+ helper T lymphocytes (HTLs) responses. Moreover, cholera toxin B (CTB) was employed as an adjuvant. Finally, EAAAK AND GPGPG sequences as linkers were considered to make a linkage between favorite peptide sequences. A multi-epitope construction was designed based on the predicted epitopes which was 270 residues in length. Further immunoinformatic analyses were carried out to assess physicochemical properties, secondary and tertiary structures, stability, intrinsic protein disorder, solubility, and allergenicity of this chimeric protein. Based on the obtained results, a soluble, and non-allergic protein with a molecular weight of 28.7 kDa was designed. Further analyses revealed that the chimeric protein is a stable protein and the predicted epitopes indicated strong potential to induce B-cell and T-cell mediated immune response. Our immunoinformatic analyses revealed that the modeled multi-epitope vaccine had appropriate properties, which can properly stimulate the immune responses of both T and B cells.